Five New Heartbeat Star Systems with Tidally Excited Oscillations Discovered Based on TESS Data - Min-Yu Li; Sheng-Bang Qian; Ai-Ying Zhou; Li-Ying Zhu; Wen-Ping Liao; Er-Gang Zhao; Xiang-Dong Shi; Fu-Xing Li; Qi-Bin Sun (The Astrophysical Journal)
Heartbeat stars (HBSs) with tidally excited oscillations (TEOs) are ideal astrophysical laboratories for studying the internal properties of the systems. In this paper, five new HBSs exhibiting TEOs are discovered using TESS photometric data. The orbital parameters are derived using a corrected version of Kumar et al.'s model based on the Markov Chain Monte Carlo method. The TEOs in these objects are examined, and their pulsation phases and modes are identified. The pulsation phases of the TEOs in TIC 266809405, TIC 266894805, and TIC 412881444 are consistent with the dominant l = 2, m = 0, or ±2 spherical harmonic. For TIC 11619404, although the TEO phase is close to the m = +2 mode, the m = 0 mode cannot be excluded because of the low inclination in this system. The TEO phase in TIC 447927324 shows a large deviation (>2 σ ) from the adiabatic expectations, suggesting that it is expected to be a traveling wave or that the pulsations are nonadiabatic. In addition, these TEOs occur at relatively low orbital harmonics, and we cautiously suggest that this may be an observational bias. These objects are valuable sources for studying the structure and evolution of eccentricity orbit binaries and extending the TESS HBS catalog with TEOs.